The social limits to growth - Horsewood, Nick (IOS Press, 2013)
The majority of Europeans nowadays are owner-occupiers. In countries where this is not yet the case, home ownership is promoted either directly or indirectly by the government, through subsidies, deregulation of the financial markets or phasing out support to the rented sector. Deregulation of national labour markets and changes to the social security system in recent years - partly due to globalization and partly to far-reaching integration in the European Union - have, weakened the links in the traditional triangle of home ownership, labour market and social security. As a result, the current growth in home ownership seems to be creating more risks for individual homeowners and for the society at large. At the same time, home ownership offers new prospects for households to assess their housing career as well as their labour market position and investment opportunities. So, home ownership has both positive as well as negative aspects for individuals and society. The research, on which this book is based, was done as part of the OSIS-project (Origins of Security and Insecurity, the interplay of housing systems with jobs, household structures, finance and social security) and funded by the EU under the 6th framework programme. The research focused on specific issues, which will give more insight into the security and insecurity aspects of home ownership across Europe and help to understand the relationship between the structural position of home ownership in different European countries.